2005
DOI: 10.1186/1477-5751-4-4
|View full text |Cite
|
Sign up to set email alerts
|

Does socioeconomic status affect mortality subsequent to hospital admission for community acquired pneumonia among older persons?

Abstract: Background: Low socioeconomic status has been associated with increased morbidity and mortality for various health conditions. The purpose of this study was twofold: to examine the mortality experience of older persons admitted to hospital with community acquired pneumonia and to test the hypothesis of whether an association exists between socioeconomic status and mortality subsequent to hospital admission for community-acquired pneumonia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 21 publications
(19 reference statements)
1
16
0
1
Order By: Relevance
“…Level 1 demographics were most commonly evaluated, and of the studies that did multivariate analyses, increased mortality was observed for older 8,16,20,[24][25][26] and male 8,20,24 patients. The pattern for race was mixed with one study showing decreased mortality 27 for blacks and two showing no statistical difference.…”
Section: Social Factors Associated With Mortality In Pneumoniamentioning
confidence: 99%
See 2 more Smart Citations
“…Level 1 demographics were most commonly evaluated, and of the studies that did multivariate analyses, increased mortality was observed for older 8,16,20,[24][25][26] and male 8,20,24 patients. The pattern for race was mixed with one study showing decreased mortality 27 for blacks and two showing no statistical difference.…”
Section: Social Factors Associated With Mortality In Pneumoniamentioning
confidence: 99%
“…However, those that did found that the presence of psychiatric comorbidity paradoxically decreased mortality 29 but there was no impact of income. 8 Only one Level 3 social factor, being a nursing home resident, significantly increased the odds of mortality (OR=1.5). 24 The use of alcohol, 30,31 distance to hospital 32 and urban neighborhood 20 were examined but not significantly associated with increased mortality.…”
Section: Social Factors Associated With Mortality In Pneumoniamentioning
confidence: 99%
See 1 more Smart Citation
“…Es ist bekannt, dass sozial bessergestellte Bevölkerungsschichten insgesamt weniger schwerwiegende Erkrankungen aufweisen und eine bessere Prognose haben [15][16][17]. Es ist bekannt, dass sozial bessergestellte Bevölkerungsschichten insgesamt weniger schwerwiegende Erkrankungen aufweisen und eine bessere Prognose haben [15][16][17].…”
Section: Limitationenunclassified
“…Other studies elsewhere show that many factors affect elderly adult mortality in different ways. However, they all highlighted the importance of socioeco-nomic status as a factor in elderly mortality (Liang et al 2003;Murata et al 2005;Sudore et al 2006;Vrbova et al 2005;Zimmer & Kwong 2004).…”
Section: Introductionmentioning
confidence: 99%